Upaya Pemerintah Daerah dalam Pembinaan Olahraga Cabang Taekwondo di Kabupaten Polewali Mandar - Irmaya Suci; Andi Gau Kadir; Indar Arifin (GOVERNMENT : Jurnal Ilmu Pemerintahan, 2011)
Abstract: This study shows that the efforts of local governments, especially sports coaching in taekwondo branch, still less than the maximum, it can be seen from the lack of government attention to the fate of the sport, particularly sport of taekwondo. The factors that affect the government's efforts towards the development of sports in Polewali Mandar consists of factors supporting and inhibiting factors. Supporting factors, among others: the HR executive, institutional support and fellow sports clubs branch Taewondo Sekabupaten Polewali, and the support of the private sector and the public, while the inhibiting factor, among others, the lack of institutional support most from the government, not their escort sustainable mechanisms, and the lack of coordination between local government and KONI Polewali Mandar.Keywords: efforts of local governments, sports coaching, sporst policyAbstrak: penelitian ini menunjukkan bahwa upaya pemerintah daerah dalam pembinaan olahraga khususnya pada cabang taekwondo, masih sangat kurang maksimal,ini dapat dilihat dari minimnya perhatian pemerintah terhadap nasib olahraga,khususnya cabang olahraga taekwondo. Adapun faktor yang mempengaruhi upaya pemerintah terhadap pembinaan olahraga di Kabupaten Polewali Mandar terdiri dari Faktor pendukung dan faktor penghambat. Faktor pendukung tersebut antara lain: adanya SDM pelaksana, dukungan kelembagaan dan sesama klub-klub olahraga cabang Taewondo seKabupaten Polewali Mandar, serta adanya dukungan dari pihak swasta dan masyarakat, sementara faktor penghambatnya antara lain, tidak adanya dukungan kelembagaan yang maksimal dari pemerintah, tidak adanya mekanisme pengawalan yang berkelanjutan, serta minimnya koordinasi antara PEMDA dan KONI Kabupaten Polewali Mandar.Kata kunci : upaya pemerintah , pembinaan olaraga,